Neutrophil Depletion Exacerbates Pregnancy Complications, Including Placental Damage, Induced by Silica Nanoparticles in Mice - Higashisaka, Kazuma; Nakashima, Akitoshi; Iwahara, Yuki; Aoki, Aiko; Nakayama, Masahiro; Yanagihara, Itaru; Lin, Ying; Nagano, Kazuya; Tsunoda, Shin-ichi; Saito, Shigeru; Yoshioka, Yasuo; Tsutsumi, Yasuo (Frontiers in Immunology, 2018)
Recent advances in nanotechnology have led to the development of nanoparticles with innovative functions in various fields. However, the biological effects of nanoparticles—particularly those on the fetus—need to be investigated in detail, because several previous studies have shown that various nanoparticles induce pregnancy complications in mice. In this regard, our previous findings in mice suggested that the increase in peripheral neutrophil count induced by treatment with silica nanoparticles with a diameter of 70 nm (nSP70) may play a role in the associated pregnancy complications. Therefore, here, we sought to define the role of neutrophils in nSP70-induced pregnancy complications. The peripheral neutrophil count in pregnant BALB/c mice at 24 h after treatment with nSP70 was significantly higher than in saline-treated mice. In addition, maternal body weight, uterine weight, and the number of fetuses in nSP70-treated mice pretreated with anti-Ly-6G antibodies, which deplete neutrophils, were significantly lower than those in nSP70-treated mice pretreated with PBS or isotype-matched control antibodies. Histology revealed that neutrophil depletion increased nSP70-induced placental damage from the decidua through the spongiotrophoblast layer and narrowed spiral arteries in the placentae. In addition, depletion of neutrophils augmented nSP70-induced cytotoxicity to fetal vessels, which were covered with endothelium. The rate of apoptotic cell death was significantly higher in the placentae of anti-Ly-6G–nSP70-treated mice than in those from mice pretreated with isotype-matched control antibodies. Therefore, impairment of placental vessels and apoptotic cell death due to nSP70 exposure is exacerbated in the placentae of nSP70-treated mice pretreated with anti-Ly-6G antibodies. Depletion of neutrophils worsens nSP70-induced pregnancy complications in mice; this exacerbation was due to enhanced impairment of placental vessels and increased apoptotic cell death in maternal placentae. Our results provide basic information regarding the mechanism underlying silica-nanoparticle-induced pregnancy complications.